The Use of Operational-Technical Measures Against Participants in the Anti-Soviet Resistance - Burinskaitė, Kristina (Genocidas ir rezistencija, 2025)
The KGB used various covert measures aimed primarily at gathering intelligence information. While agents were the KGB’s main tools, in some cases covert technical measures proved more effective in collecting information. The use of such measures was strictly regulated, and they could only be employed by those who had already exhausted other options. Like agents, operational-technical measures could also be used for other repressive purposes, such as gathering information for criminal proceedings or preventive activities, making them integral to the repression policies. Although they were mostly applied to monitor the movement of foreign nationals in Lithuania, they also played an important role in countering the activities of participants in the Lithuanian anti-Soviet resistance movement. Cases documented in KGB files show that these measures were aimed not only at uncovering participants in the anti-Soviet movement, but also at identifying associated individuals and dismantling the group’s activities while gathering material for criminal proceedings. These measures rarely achieved their goals; however, the dissemination of the Lithuanian Catholic Church Chronicle in Lithuania and the West indicates that the KGB remained mostly an observer, although some individuals were harmed.
Keywords: KGB; anti-Soviet resistance movement; technical measures; self-publishing